THE PROPRIETARY DIMENSION OF SOCIAL COMMUNICATION AND THE ANTITRUST LEGAL APPROACH: CONTRIBUTION TO PLURALISM IN BRAZILIAN MEDIA? - Henrique Lopes Figueiredo, Eduardo; Barbosa Fernandes, Sara (Revista da Faculdade de Direito do Sul de Minas, 2022)
The present work questions the paradoxical proprietary dimension of the media in Brazil. Although constituted by private companies, goes back to its formation to public privileges. This dimension of communication envolves contemporary public sphere in the structuring of the brazilian social media. It is necessary point out as a start that what should be its base of this exploration: the pluralism. It aims to analyze the construction of media ownership in Brazil and the possibility of applying existing legal mechanisms, specifically antitrust instruments to the media. Based on the perception of the concentration of media ownership, based on critical dialectical thinking as methodology, it is proposed to examine the importance of pluralism to the media, concluding that the brazilian media are constituted under Constitutional system in the form of an oligopoly, making it possibilities to apply antitrust mechanisms as a way of contributing to network pluralism and public opinion formation.